Primary and metastatic malignancies of the lung: Retrospective analysis of the CT-guided high-dose rate brachytherapy (CT-HDRBT) ablation in tumours <4 cm and ≥4 cm. Issue 108 (November 2018) - Jonczyk, Martin; Collettini, Federico; Schnapauff, Dirk; Geisel, Dominik; Böning, Georg; Feldhaus, Felix; Wieners, Gero; Hamm, Bernd; Gebauer, Bernhard
Highlights: CT-HDRBT achieves higher LTC and OS in primary and secondary pulmonary tumours smaller than 4 cm. Even pulmonary tumours ≥4 cm can be securely treated with CT-HDRBT. PFS is not influenced by local ablation. Abstract: Background: Minimal invasive local therapies are alternative treatment options in patients with primary and metastatic lung malignancies being not eligible for resection. However, thermal ablations are often limited by large tumour volumes. Purpose: To evaluate the efficacy and safety of CT-HDRBT in pulmonary tumours ≥4 cm compared to smaller tumours. Material and methods: In this retrospective study, 74 consecutive patients (mean age: 63 ± 12; m: 39, w: 35) with a total of 175 tumours treated in 132 interventions were enrolled between October 2003 and September 2016. Primary and assisted local tumour control (LTC), progression free survival (PFS) and overall survival (OS) after first CT-HDBRT were identified for two subgroups with tumours <4 cm (A) as well as ≥4 cm (B) using the Kaplan-Meier-Method. Radiation parameters and side effects were recorded. Log-Rank-Test and Mann-Whitney-U-Test were performed for statistical analyses with p-values <0.05 considered as significant. Results: There was no statistical difference in coverage with prescribed radiation dose (A:19.78 ± 8.62 mm (range 5–39 mm), 99.56 ± 0.99%; B:61.70 ± 21.09 mm (41–100 mm), 94.81 ± 7.19%, p = 0.263). LTC rates after 0.5-, 1-, 2-, 3- and 5-years were higher in A compared to B (A:85%/74%/63%/60%/46%, B:71%/37%/32%/32%/32%) with longer primary (A:11months, B:5months, p = 0.003) and assisted LTC (A:9months B:20months, p = 0.339). Longer OS was observed in A (A:18.5months, B:14.5months, p = 0.011) with longer OS rates (A:96%/87%/60%/48%/19%, B:92%/73%/20%/20%/0%). Complication assessment revealed no bleedings, 16.6% pneumothoraxes and 48.5% of mild radiation fibrosis without clinical symptoms. Conclusion: In conclusion, higher LTC and OS were observed in patients with primary lung malignancies <4 cm. Nevertheless, CT-HDRBT is a safe and feasible alternative even in larger tumours ≥4 cm.